Rolnictwo ekologiczne i zrównoważone - doświadczenia na przykładzie województwa opolskiego - Kuczuk, Anna (Ecological and sustainable agriculture - experience of the Opolskie voivodship, 2007)
The traditional agricultural production that dominated for many years has provoked many negative conseąuences in natural environment and social costs. At present it is possible to observe an inerease of interest in ecological and sustainable productions. Both of them have different rules of the soil, work and Capital management than conventional system. In the Opolskie voivodship the interest in altemative production methods, is growing every year. The implementation of ecological production in agriculture is very important on account of the presence of natural areas and ecological consciousness of farmers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 369-377